Agilik@home: A randomized controlled trial protocol to evaluate the effects of home-based training with the Agilik powered KAFO in children with cerebral palsy and crouch gait - Roberta Nossa; Fabio Alexander Storm; Eleonora Diella; Riccardo Riboni; Luca Emanuele Molteni; Mattia Chiappini; Cristina Maghini; Elena Beretta; Roberta Nicotra; Sara Abbondio; Carolina Ferrante; Annalisa Cotardo; et al. (PLoS ONE, 2026)
Background Cerebral palsy (CP) is the most common neuromotor disability in children and often results in spastic diplegia, which can lead to crouch gait. This gait pattern, resulting from weakness predominantly in the extensor muscles and spasticity mainly affecting the flexors, is characterized by excessive knee flexion, insufficient hip extension, and excessive ankle dorsiflexion, which together can progressively impair walking. The Agilik powered knee-ankle-foot orthosis is designed to enhance knee extension and potentially improve gait in children with CP. Here we present the protocol of a study that aims to evaluate the clinical effectiveness of Agilik in a domiciliary setting. Methods According to this protocol, the multicentre randomized controlled trial will enrol 40 children with CP (aged 5–17 years) exhibiting crouch gait. Participants will be randomly assigned to either the Intervention Group, which will receive training with the Agilik device, or the Control Group, which will maintain their standard routines and therapies. All participants will undergo physical examination and baseline assessments. Then, while the Control Group continues the usual care, the Intervention Group will begin the Agilik program, including three device fitting visits, 4/5 weeks of hospital training, and two months of home-based sessions. Both groups will be evaluated at three time points: baseline, after the intervention, and at a one-month follow-up. Primary endpoints include the 6-Minute Walking Test and Knee Extension in Mid-Stance computed during gait analysis. Secondary endpoints assess gross-motor abilities, gait speed, 3D gait analysis with electromyography, joint range of motion, muscle length, self-perceived performance, spasticity, and balance. Additionally, the Intervention Group will provide feedback on the usability and acceptability of the device, and on cognitive, behavioural and affective engagement. Discussion This trial will provide valuable insights into the effectiveness of the Agilik device in children with CP and crouch gait. It will help emphasizing the potential benefits of the device on daily living activities and gait performance. The findings could influence clinical practice and guide future interventions for managing crouch gait in CP, potentially leading to enhanced quality of life for these children. Trial registration The trial has been registered the 30 th September 2024 on ClinicalTrials.gov with the identifier NCT06622655.